Regional anesthetic techniques are an alternative to general anesthesia for infants with Pompe's disease - WALKER, ROBERT W.M.; BRIGGS, GERAINT; BRUCE, JAMES; FLETCHER, JOAN; WRAITH, E.D. (Pediatric anesthesia, 2007)
Summary Pompe's disease or glycogen storage disease type II is a genetic disorder affecting skeletal and cardiac muscle. The infantile form is associated with gross hypertrophic cardiomegaly and death in the early years. General anesthesia is associated with potential major morbidity in these patients. We present our experience of regional anesthetic blocks used in five patients with the infantile form of glycogen storage disease type II with and without sedation for 11 surgical procedures during a clinical trial of replacement therapy for this condition. Both femoral nerve blockade and caudal epidural blockade were used with good result. The relative merits of the type of block are discussed in addition to the choice of sedation and risks of general anesthesia. The avoidance of general anesthesia in the newly presenting patient with Pompe's disease may reduce potential morbidity until enzyme replacement has been established.